2017
DOI: 10.1038/leu.2017.317
|View full text |Cite
|
Sign up to set email alerts
|

Targeting acute myeloid leukemia by drug-induced c-MYB degradation

Abstract: Despite advances in our understanding of the molecular basis for particular subtypes of acute myeloid leukemia (AML), effective therapy remains a challenge for many individuals suffering from this disease. A significant proportion of both pediatric and adult AML patients cannot be cured and since the upper limits of chemotherapy intensification have been reached, there is an urgent need for novel therapeutic approaches. The transcription factor c-MYB has been shown to play a central role in the development and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 51 publications
7
96
0
Order By: Relevance
“…Recently, xenografting and the first MYB‐NFIB‐positive cell line (UM‐HACC‐2A) have been established and represent interesting tools to explore novel therapeutic possibilities . Therapeutically, MYB‐targeted antisense oligodeoxynucleotides (G4460; INX‐3001; LR3001) have not been effective in clinical trials ; however, several lines of evidence suggest that MYB is a promising therapeutic target . Currently, the first clinical trial of a therapy that directly targets MYB, in combination with an anti‐PD‐1 immune checkpoint inhibitor, opened (MYPHISMO, NCT03287427), and the first patient with ACC received her first infusion of the MYB DNA vaccine in September 2018 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, xenografting and the first MYB‐NFIB‐positive cell line (UM‐HACC‐2A) have been established and represent interesting tools to explore novel therapeutic possibilities . Therapeutically, MYB‐targeted antisense oligodeoxynucleotides (G4460; INX‐3001; LR3001) have not been effective in clinical trials ; however, several lines of evidence suggest that MYB is a promising therapeutic target . Currently, the first clinical trial of a therapy that directly targets MYB, in combination with an anti‐PD‐1 immune checkpoint inhibitor, opened (MYPHISMO, NCT03287427), and the first patient with ACC received her first infusion of the MYB DNA vaccine in September 2018 .…”
Section: Discussionmentioning
confidence: 99%
“…We chose this drug due to its efficiency in inducing differentiation (in combination with ATRA) at relatively low doses. Recent studies showed that mebendazole reduces growth and viability of AML cell lines, and induces proteasomal degradation of the oncogenic TF c-MYB through inhibition of its association with the heat shock protein 70 (HSP70) chaperone system 25,48 . However, these studies did not investigate the effects of mebendazole on myeloid differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…There is previous evidence that medendazole has anti-leukemic properties in AML 25 and indirectly interacts with tubulins according to the Therapeutic Target Database (TTD) 37 . Therefore we chose to experimentally test it, although it does not have expressed targets at 0h.…”
Section: Identification Of Cmap Drugs For Experimental Validationmentioning
confidence: 99%
See 2 more Smart Citations